鋼管表面の熱間における凹凸欠陥検出を目的とした「ツイン投光差分方式」の開発 - 飯塚, 幸理; 山崎, 孝博; 大野, 紘明; 大重, 貴彦; 腰原, 敬弘; 小川, 晃弘; 児玉, 俊文 (鉄と鋼, 2018)
In optical surface inspection of steel products under hot conditions, overdetection caused by signals from harmless features such as scale and surface texture is usually a problem. Therefore, the authors proposed a new inspection technique called the “twin-illumination and subtraction technique,” which is able to remove only harmless signals, based on the finding that most harmful defects on these products have concave shapes, whereas most harmless features that might be overdetected have flat or convex shapes. As an application of this technique, after laboratory tests to confirm its effectiveness, we set up a prototype system for hot pipes which have poor surface properties. Although harmless signals from flat surfaces could be removed as expected, harmless signals from convex surfaces such as peeling scale and micro-surfaces which cause specular reflection conditions remained in addition to harmful signals from concave defects. To improve detectability, we introduced a discrimination method based on the characteristic bright/dark patterns of concave defects, a detection and decision tree judgment function using features from images and so on. At present, the installed prototype system presents information concerning detected defects to operators. As a result, we have confirmed that the system has sufficient performance for prevention of large outbreaks of nonconforming products and is an effective technique for detection of poor surface condition.